Direct measurement of leaf area index in a deciduous needle-leaf forest, eastern Siberia - Shin, Nagai; Kotani, Ayumi; Sato, Tomonori; Sugimoto, Atsuko; Maximov, Trofim C.; Nogovitcyn, Aleksandr; Miyamoto, Yumiko; Kobayashi, Hideki; Tei, Shunsuke (Polar Science, 2020)
Accurate calculation of leaf area index (LAI) in boreal forests, which are vulnerable to climate change and have insufficient ground-truth data, is an important but challenging task when evaluating the spatio-temporal variability of ecosystem structures and functions (photosynthesis and evapotranspiration). By applying a direct method, we calculated the LAI of multiple forest layers (i.e., overstory of larch; understory of birch, willow, and alder; and floor vegetation) in a deciduous needle-leaf forest with a somewhat open canopy in eastern Siberia. We performed field studies that included logging one overstory larch tree, harvesting leaves of larch and floor vegetation (e.g., Vaccinium vitis-idaea), sampling leaves of understory trees, and measuring the architecture and morphology of overstory and understory trees and leaves. The plot-scale LAIs of larch overstory, understory trees, and floor vegetation were 1.30, 0.50, and 0.51, respectively, for a total of 2.31. Sum of our plot-scale LAI of larch overstory and understory trees was similar to previously reported results based on indirect methods. Our results indicate that LAI of understory trees and forest floor vegetation is important to improve the accuracy of total LAI of a deciduous needle-leaf forest with a somewhat open canopy in eastern Siberia. journal article